Patients' characteristics and their ideas about physical medicine and rehabilitation practice [FIZIK TEDAVI VE REHABILITASYON KLINIGINE BASVURAN HASTALARIN BU BRANS HAKKINDAKI GORUSLERI, BILGILERI VE DEMOGRAFIK OZELLIKLERI] - (:unkn) unknown (My University, 1995)
The aim of this survey was to develop a profile of patients' ideas about Physical Medicine and Rehabilitation (PMR) practice in Turkey and to assess demographic characteristics of our patients. A questionnaire of ten items was filled-by 160 patients (37 male, 123 female) prior to examination in our outpatient clinic. In the first six questions, we assessed basic demographic information such as the patients' name, age, sex, place of birth, occupation and educational status. Then, reasons for preferring our clinic were inquired. The patients were asked to respond whether they had been examined by other physicians prior to this visit. Lastly, they were asked to phrase in their own words what conditions they thought a physiatrist dealt with. Our results revealed that housewives constituted the highest percentage of our patient population followed by retired employees. The majority of the patients could not define PMR practice accurately and their first choice for remedy was not physiatry clinics.
Keywords: Patient awareness; Patient characteristics; Physical medicine; Rehabilitation